Corporate Risk Management - Donald H. Chew (Columbia University Press, 2008)
The theory of corporate risk management has changed a lot in the past 25 years. And so has corporate practice, mainly in ways predicted by the theory. In the 1980s and well into the 1990s, most large companies had a â€œrisk managerâ€ whose main job was to oversee the fi rmâ€™s insurance purchases. At the same time, fi nancially savvy corporate trea sur ers, with little or no input from risk managers, began using newfangled securities called â€œderivativesâ€ to hedge the fi rmâ€™s interest rate and currency exposures. In many of these companies, especially those where the trea sury was encouraged to view itself as a profi t center, the trea sur ers followed a practice known as â€œselective hedging.â€ In practice, selective hedging meant leaving exposures unhedged (or, in some cases, maybe even enlarging them) when so directed by the trea sur erâ€™s â€œviewâ€ of future prices. The main purpose of such hedging was to pad or smooth the corporate profi t and loss statement, with the idea that shareholders place a premium on earnings stability, no matter how achieved. But in the last 10 years, the scope and mission of corporate risk management have expanded well beyond insurance and opportunistic hedging to include all kinds of corporate operating and strategic risks. And, as oversight and control of these once compartmentalized activities has become more centralized, the corporate risk manager has given way to the â€œchief risk offi cer,â€ a senior management function increasingly overseen by the board of directors. In many companies the mission of corporate risk management, once concerned mainly with smoothing out bumps in the earnings trajectory, has become protection of the fi rmâ€™s â€œfranchise valueâ€â€”that is, protection of all the fi rmâ€™s major sources of future earnings power. As Bob Anderson, executive director of the Committee of Chief Risk Offi cers, notes in the roundtable discussion that ends this book, corporate risk management is no longer â€œjust a series of isolated transactions; itâ€™s a strategic activity . . . [that] encompasses everything from operating changes to fi nancial hedging to the buying and selling of plants or new businessesâ€”anything that affects the level and variability of cash fl ows going forward. When viewed in this light, risk management is clearly a se nior management responsibility, one that requires input from and coordination of the company at all operating levels.â€